Gender analyses on acceptance level of Reggio Emilia early childhood development program among parents in rural areas, Katsina State, Nigeria - Abdullahi, Ibrahim (2020)
The early childhood development is critical for any country in the world. Thus, the readiness of parents in rural areas of developing countries for acceptance of early childhood development program is essential. Reggio Emilia Approach in Early Childhood Development (REA-ECD) was launched by Nigeria in 2014, and Katsina state in 2015. This REA-ECD proved to be successful within rural communities in the face of parents’ acceptance. This study aims to examine by sex disaggregate the backgrounds of the parents who accepted and enrolled their children in REA-ECD program, their households’ backgrounds, their acceptance level, and REA-ECD acceptance predictors. The significant predictors would be useful in future programs and acceptance studies. The main theories underlined this study were Gender Role, Technology Acceptance and Innovations Diffusion Theories, supporting sex-disaggregated measurement of REA-ECD acceptance (dependent variable). Besides, Vygotsky Sociocultural Learning Theories were used to support the respondents and households’ backgrounds as (independent variables). The background of the study was the parents who enrolled their children in REA-ECD program. They were selected from six Local Government Areas (LGA) of the state. The instruments for data collection were developed through adaption from the previous studies. The data were collected through the administered questionnaires. The total of 405 questionnaires (93.75%) from respondents were screened and considered for the research analyses. Respondents and households’ backgrounds were captured in descriptive analyses. The REA-ECD acceptance levels were through mean and S.D, and association of respondents’ sex with acceptance was determined by Chi-Square test. Binary Logistic Regression with dichotomous dependent variable; scores ≥ 80% (1) was used to measure models’ predictors of REA-ECD acceptance. Major findings show Means age of respondents was 38.99 years, monthly income for males and females were USD 154.6 and USD122.3. respectively, and years in marriage is 13.6. Findings show 50.8% of males and 30.4% of females’ respondents were employed. Male at 59.2% and females at 30.9% attended tertiary education. Male-headed household means monthly income is USD304.2, while the female-headed household is USD292.3. Households at 62.4% have 3-6 members, 80.5% enrolled children at 4-5 years and 74.3% prepared REA-ECD. There is no significant association (p>0.05), between the level of acceptance and respondents’ sex. The four models of the study were significant (p<0.05),BLR statistics obtained p≤0.05 in Omnibus Tests of Model Coefficients. This indicates that components variables of Models were sufficient, and models fit to predict the likelihood of high REA-ECD acceptance. Hosmer and Lemeshow test of goodness of fit statistics at p>0.05, indicates the variables in models were linearly related with log odds of REA-ECD acceptance. The findings revealed the needs for policy to focus more on both females and males for development programs like REA-ECD. This study may be useful guidelines for rural areas in northern Nigeria policies.